Unraveling the Impact of Psychological Contract Breach on Work Engagement and Life Satisfaction in Generation Z - Yusup, Alfiah Fill Kholqi; Hendryadi, Hendryadi (Research of Economics and Business, 2025)
This study examines the relationship between psychological contract breach, work engagement, and life satisfaction in Generation Z individuals working in various sectors in Jakarta. Using a quantitative approach, data were collected through questionnaires distributed to 158 respondents aged 21 to 27 years working in various sectors. The sampling technique employed was purposive sampling, while data analysis was conducted using Structural Equation Modeling (SEM) with Confirmatory Factor Analysis (CFA) and regression tests via Jamovi software. The study's results indicate that psychological contract breach has a negative and significant impact on life satisfaction. In contrast, life satisfaction has a positive and significant impact on work engagement. In addition, psychological contract breach also harms work engagement, both directly and indirectly, through its impact on life satisfaction. This study provides new insights into the complex dynamics between psychological contract breach and work engagement, especially in understanding the engagement of Generation Z employees.